Wells and production functions - Ganat, T.A.-A.O. (Springer, 2020)
After identifying potentially feasible fields and at the beginning of an oil field development plan, once the oil field dimensions have been allocated, engineers determine the number of wells needed to meet production requirements and the method of extraction of the liquid hydrocarbons. Â© The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.